PENGARUH PEMBERIAN AROMATERAPI PEPPERMINT TERHADAP MUAL MUNTAH PADA IBU HAMIL DI KOTA PEKANBARU - Sellia Juwita; Nova Yulita; Jumiati Jumiati; Husna Farianti Amran (Ensiklopedia of Journal, 2023)
Pregnancy is a physiological condition that can be followed by a pathological process that threatens the condition of the mother and fetus. One of the problems that can occur during pregnancy TM 1 and 2 is nausea and vomiting. Nausea is an unpleasant feeling related to feeling sick or urges to vomit, while vomiting is the expulsion of stomach contents through the mouth due to involuntary muscle spasms. Nausea and vomiting occur in 60-80% of first pregnant women (primigravidas) and 40-60% in multigravida mothers. Constant nausea and vomiting will cause complications for the mother and the fetus. The aim of this study was to see the effect of peppermint aromatherapy on nausea and vomiting in pregnant women. This type of research is a quantitative study using a quacy experimental research design using two group pretest-posttest design. The population in this study were pregnant women with TM 1 and 2, using a purposive sampling technique with a total sample of 30 people. Data processing used univariate and bivariate analysis. Bivariate analysis used the T test. The results showed that peppermint aromatherapy affected the reduction of nausea and vomiting in pregnant women with TM 1 and 2 with a value of ρ: 0.000 <0.05.